CONCEPTUAL DIRECTIONS FOR DEVELOPING MODEL OF REGIONAL CENTER OF CARDIOLOGY AND CARDIOVASCULAR SURGERY BASED ON PUBLIC-PRIVATE PARTNERSHIP PRINCIPLES - Ivanyuk, V. (Актуальні проблеми сучасної медицини: Вісник Української медичної стоматологічної академії, 2021)
The aim of this study is to substantiate conceptual directions for developing the model of regional center of cardiology and cardiovascular surgery based on the principles of public-private partnership. Material and methods. General scientific methods of analysis, synthesis, generalization, interpretation of scientific date, as well as systemic and structural functional approaches are used in the study. Results. There have been identified four components that are the basis for the conceptual directions in developing the model of regional center of cardiology and cardiovascular, this is a set of methods for a model development, modeling principles, the logical structure formation of the model functioning and modeling technology. At the same time, the conceptual directions of the model development serve as a practical methodology for the complex process of regional center of cardiology and cardiovascular modeling implementation and a strategy for long-term collaboration between the state and business in solving the socially significant task of innovative high-tech cardiological care, which is being created for the population of the region. Conclusions. Conceptual directions serve as a methodological tool for the creation of the modern model of a medical institution with private capital, market mechanisms, ensuring a stable economic progression and the possibility of developing technical base.